Dynamic authentication protocols for advanced security in federated metaverse systems - Hasan, Md Fuad; Ashfaq, F.M.; Chowdhury, Ahmed Awsaf; Hamim, Shoeb Islam; Rahmani, Mustafiza (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.